Consumer understanding of Consumer Celebration Month 2010 theme: "Consumer Power: 1 Consumer 1 Voice" - Masud, Jariah; Haron, Sharifah Azizah (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
The theme for Consumer Celebration Month 2009 was Consumer Power: 1 Consumer 1 Voice (Kuasa Pengguna: 1 Pengguna I Suara). What is the meaning of this theme to consumers? The purpose of this study is to examine what Malaysian consumers understand about the theme. Data collected by the state level Ministry’s officials among consumers in August to December 2009 were used for this analysis. Consumers were asked to choose which of the 10 statements listed explained the theme. A total of 7026 respondents participated in this self administered study. More than half of the respondents (54%) were females and two-thirds comprised of Gen X, 30.5% Gen Y and there were only 7% Baby Boomers generation. Two thirds of the respondents (64%) gave the correct answer (united consumers can influence change the market). Higher percentage of males, married, Malays and The Baby Boomers provided the right answer compared to other groups. Binary logistic analysis with dependent variable correct answer with independent variables of respondents background revealed that Gen Y had 1.8 times and Gen X had 1.5 times likelihood of giving the wrong answer compared to Baby Boomers. Those with tertiary education were more likely to provide the right answer. Efforts should be focused to educate Gen X and Gen Y to ensure they had good knowledge and behave effectively in the market.